2010
DOI: 10.21000/jasmr10010582
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Performance of Artificially Regenerated American Chestnut on Reclaimed Mine Sites

Abstract: The use of SMCRA approved practices for mined land reclamation has resulted in arrested succession throughout many areas of central Appalachia. The combination of heavily compacted soils and the addition of aggressive, often nonnative, grasses and forbs creates an environment characterized by high soil bulk density and aggressive ground-layer competition. This results in a situation where trees are unable to recruit and thus many lands are unable to return to original forest cover through natural processes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 10 publications
0
19
5
Order By: Relevance
“…Two of these studies also assessed survival of trees planted as unsheltered seeds. In Ohio, McCarthy et al [12] found a significant sheltering effect; however, survival of unsheltered trees was around 55% in their study, which was much greater than survival of unsheltered trees found in our study. Similarly, unsheltered chestnuts in West Virginia survived well through four growing seasons (57%).…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Two of these studies also assessed survival of trees planted as unsheltered seeds. In Ohio, McCarthy et al [12] found a significant sheltering effect; however, survival of unsheltered trees was around 55% in their study, which was much greater than survival of unsheltered trees found in our study. Similarly, unsheltered chestnuts in West Virginia survived well through four growing seasons (57%).…”
Section: Discussioncontrasting
confidence: 95%
“…Other studies report first year survival of sheltered trees planted as seeds: 76% in Virginia [15] and >80% in Ohio [12]. These values are higher than first-year survival in our study (65%).…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations